PENGARUH EFESIENSI BIAYA BAHAN BAKU DAN BIAYA TENAGA KERJA TERHADAP VOLUME PRODUKSI PADA CV â€œ JATI JAYA â€ SINGARAJA - Ni Kadek Ayu Trisnadewi (ARTHA SATYA DHARMA, 2021)
This study aims to determine the effect of raw material costs and labor costs on production Abstract. This study aims to determine the effect of raw material costs and labor costs on production volume partially or simultaneously at CV Jati Jaya Singaraja for the 2016-2020 period. The research method used in this study is a descriptive and verification research method using a quantitative approach. The population of this study is the annual financial report of CV Jati Jaya and the sample was taken for 5 years for the 2016-2020 period.The results of this study indicate that the sig value of the influence of Raw Material Costs on Production Volume is 0.006 smaller than the value of 0.05, (0.006 <0.05) so Ho is rejected and Ha is accepted. This means that statistically at = 5%, the cost of raw materials has a significant (significant) effect on the Production Volume of CV Jati Jaya Singaraja. Thus, the first hypothesis proposed in this study, namely that there is a positive and significant influence on the cost of raw materials on production volume at CV Jati Jaya Singaraja, is proven to be true. The sig value of the motivational effect on labor costs is 0.018, which is smaller than the value of 0.05, so Ho is rejected and Ha is accepted. This means that statistically at = 5%, the cost of raw materials has a significant (significant) effect on the production volume at CV Jati Jaya Singaraja. . Thus, the second hypothesis proposed in this study, namely that there is a positive and significant influence on the Cost of Manpower on the Production Volume of CV Jati Jaya Singarja, is proven to be true.